Precision drugging of the MAPK pathway in head and neck cancer - Hoi-Lam Ngan; Chun-Ho Law; Yannie Chung Yan Choi; Jenny Yu-Sum Chan; Vivian Wai Yan Lui (npj Genomic Medicine, 2022)
Abstract The mitogen-activating protein kinase (MAPK) pathway is central for cell proliferation, differentiation, and senescence. In human, germline defects of the pathway contribute to developmental and congenital head and neck disorders. Nearly 1/5 of head and neck squamous cell carcinoma (HNSCC) harbors MAPK pathway mutations, which are largely activating mutations. Yet, previous approaches targeting the MAPK pathway in HNSCC were futile. Most recent clinical evidences reveal remarkable, or even exceptional pharmacologic vulnerabilities of MAPK1-mutated, HRAS-mutated, KRAS-germline altered, as well as BRAF-mutated HNSCC patients with various targeted therapies, uncovering diverse opportunities for precision drugging this pathway at multiple “genetically condemned” nodes. Further, recent patient tumor omics unveil novel effects of MAPK aberrations on direct induction of CD8+ T cell recruitment into the HNSCC microenvironment, providing evidences for future investigation of precision immunotherapy for this large subset of patients. MAPK pathway-mutated HNSCC should warrant precision therapy assessments in vigorous manners.